Strategi City Branding Jakarta Sebagai Ibukota Multikultural; Studi Deskriptif Kualitatif Dinas Pariwisata Dan Kebudayaan DKI Jakarta - Rosanah Rosanah (PRoMEDIA, 2020)
Abstract Jakarta as the nation's capital that reflects "miniature Indonesia" with a diversity of cultures, ethnicities and religions is one in the frame of "Unity in Diversity". Based on the Vision and Mission of the DKI Jakarta Governor for the 2017-2022 period, the DKI Jakarta Tourism and Culture Office through the Domestic Marketing Promotion Section will conduct a City Branding in order to realize Jakarta as a Multicultural Capital for all various groups and communities in the capital. City Branding is a marketing strategy in order to build a city's identity. Imaging the city requires each region to create an image of a particular city that shapes the character of the city that is intended to shape and enhance tourism and cultural potential. Multiculturalism with its various uniqueness and the slogan "Enjoy Jakarta" as the identity of the city of Jakarta is a strategy to package as city image of Jakarta as a tourist and cultural destination with international standards. This study aims to describe the activities of the Department Tourism and Culture of DKI Jakarta Province in conducting the City Branding of Jakarta as the Multicultural Capital. This research uses descriptive qualitative with documentation study and interviews as a primary data source. The results of research on City Branding Jakarta as the Multicultural Capital are carried out through the Integrated Marketing Communication strategy, namely: Promotion, Advertising, Direct Selling, Personal Selling and Public Relations. Among them through innovative local cultural collaborative events and various international scale events, infrastructure development of the capital and tourist destinations, as well as the use of various social media platforms and online media. The implementation of City Branding of the Jakarta Tourism and Culture Office also establishes cooperation and involves various parties such as local communities, investors and stakeholders such as synergy with the "Jakarta Tourism" community, through exploration, elaboration and collaboration of various tourism and cultural potentials in realizing Jakarta not only as a city transit but can increase the number of domestic and foreign tourists. The parameters of success of the City Branding strategy can be seen among others based on an increase in the number of tourists and accommodation, The Number of Tourism, Length of Stay (LoS), Money Circulation, and various awards won by the Department of Tourism and Culture and the Governor of DKI Jakarta Province”. Keywords: Communication Strategy, City Branding, Multicultural CapitalAbstraksiJakarta sebagai Ibukota Negara yang merefleksikan “miniatur Indonesia”, dimana keberagaman budaya, suku, etnis, dan agama kumpul menjadi satu dalam bingkai “Bhineka Tunggal Ika”. Mengacu pada Visi dan Misi Gubernur DKI Jakarta Periode 2017-2022, Dinas Pariwisata dan Kebudayaan DKI Jakarta melalui Bidang Destinasi Pemasaran Seksi Promosi Dalam Negeri melakukan City Branding dalam rangka mewujudkan Jakarta sebagai Ibukota Multikultural yang merangkul seluruh golongan dan komunitas yang ada di ibukota. City Branding adalah strategi pemasaran dalam rangka membangun identitas sebuah kota. City Branding menuntut setiap daerah untuk berlomba menciptakan citra tertentu sehingga terbentuklah city image yang menjadi karakter sebuah kota yang bertujuan untuk membentuk dan meningkatkan potensi wisata dan budaya. Multikulturalisme dengan berbagai keunikannya dan slogan “Enjoy Jakarta” sebagai identitas kota Jakarta merupakan strategi Packaging sebuah brand atau City Image Ibukota Jakarta sebagai tujuan wisata dan budaya dengan standar Internasional”. Penelitian ini bertujuan untuk mendeskripsikan aktivitas Dinas Pariwisata dan Kebudayaan Provinsi DKI Jakarta dalam melakukan City Branding Jakarta sebagai Ibukota Multikultural. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan studi dokumentasi serta wawancara sebagai sumber data primer. Berdasarkan hasil penelitian, City Branding Jakarta sebagai Ibukota Multikultural dilakukan melalui strategi Integrated Marketing Communication, yaitu: Promotion, Advertising, Direct Selling, Personal Selling dan Public Relations. Diantaranya melalui event kolaboratif budaya lokal yang Inovatif serta berbagai event skala Internasional, pembangunan infrastruktur ibukota dan destinasi wisata, serta pemanfaatan berbagai platform media online dan media sosial. Implementasi City Branding Dinas Pariwisata dan Kebudayaan DKI Jakarta juga menjalin kerjasama dan melibatkan berbagai pihak seperti masyarakat lokal, investor dan stakeholders seperti sinergitas dengan komunitas “Jakarta Tourism”, melalui ekplorasi, elaborasi dan kolaborasi berbagai potensi wisata dan budaya dalam rangka mewujudkan Jakarta bukan hanya sebagai kota transit semata akan tetapi dapat meningkatkan jumlah wisatawan dalam dan luar negeri. Parameter keberhasilan dari strategi City Branding diantaranya dapat dilihat berdasarkan adanya peningkatan jumlah wisatawan dan akomodasi, The Number of Tourism, Length of Stay (LoS), Peredaran uang, serta berbagai penghargaan yang diraih Dinas Pariwisata dan Kebudayaan dan Gubernur Provinsi DKI Jakarta.Keywords: Strategi Komunikasi, City Branding, Ibukota Multikultural.